Comment étudier les classes populaires contemporaines ? De l’analyse statistique d’un espace social à une enquête par monographies de ménages - Amossé, Thomas; Bernard, Lise; Cartier, Marie; Lechien, Marie-Hélène; Masclet, Olivier; Schwartz, Olivier; Siblot, Yasmine (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
This text presents the approach implemented in a collective research on the condition and lifestyles of workers and employees in contemporary France. This research aims to shed light on the contemporary features of the working classes and explores three dimensions: consumption practices, relations with the future and stabilization resources; the gendered division of roles; and sociability and family and local relations between the two. The research combines quantitative analyses of official statistics surveys with in-depth monographs of households with relative economic stability.